AUDITORÍA DE GESTIÓN EN EL COMANDO DE LA POLICÍA NACIONAL DEL ECUADOR DISTRITO 1 ZONA 7 DE LA SUBZONA N°11 LOJA PERIODO 2015 - AZANZA YERE, TANIA JACKELINE (2016)
The development of the thesis: "AUDIT MANAGEMENT IN COMMAND OF THE NATIONAL POLICE OF ECUADOR, WARD 1 ZONE 7 of subarea No. 11 LOJA PERIOD 2015" is oriented to the study, implementation and verification of compliance with the activities planned by the administrative and operational aspects of the institution, through management indicators that helped determine the efficiency, effectiveness and economy with which the assigned functions are developed. For the implementation of this practice and methodological condition is deductive application, being a highly technical career; however, for the development of components and phases it relied on auxiliary methods such as inductive, descriptive, analytical, mathematical method; In addition, a survey was applied to officials in general, same that allowed us to determine the preliminary knowledge of the institution being audited, and the current situation of the institution and this sequence with each of the phases until the end was used with the final report, and schedule follow-up was conducted based on the existing rules for entities of public law and applied procedures contained in the manual audit. According to the results of the work of special qualifications, it was determined that the entity under study have not been implemented audits 5 on the other there is personal side that do not perform functions that are commensurate with their professional profile, and receive no training. Also during the period under review have not been implemented management indicators for determining the degree of compliance of activities in terms of efficiency, effectiveness and economy Given this, it was recommended to the Command of the National Police of Ecuador, District 1 Area 7 subarea No. 11 Loja "conduct performance audits periodically to the Internal Control Standards is observed updated. At the end of this research work a report was submitted to the District Commander of the respective findings and valid, reasonable and timely recommendations to assist the improvement of the inSTITUTION